The Synergy of Islam and Local Tradition: A Study of Social Sufism Values Within the Sambelien Tradition in Malangsari, Banyuwangi, Indonesia - Azisi, Ali Mursyid; Syarifudin, Syarifudin; Yazid, Muhammad Afiq bin Mohd (Sunan Kalijaga: International Journal of Islamic Civilization, 2023)
This study delves into the synergy of Islam and local culture, particularly the "sambelien" tradition observed by the Malangsari community. This tradition serves as a poignant expression of welcome for Eid al-Fitr, encapsulating profound social Sufism values. Rooted in the community's collective aspiration for forgiveness and joy during this significant Islamic celebration, sambelien yields substantial social benefits. Employing a qualitative approach with a phenomenological orientation, the researcher conducted a thorough investigation, gathering primary and secondary data. The study draws upon Berger & Luckman's social construction theory, encompassing subjective reality, symbolic reality, and objective reality, as well as the processes of externalization, objectification, and internalization. The article aims to unravel the core values embedded within the sambelien tradition through descriptive exploratory analysis. The findings illuminate the tradition as a cherished practice among rural communities in the Malangsari region, where joint prayers in mosques or langgar symbolize communal celebration. The act of seeking forgiveness from Allah SWT, following the fasting period of Ramadan, underscores the spiritual significance of this tradition. The local community acknowledges the presence of Sufism and social values, viewing the tradition as a reflection of maintaining habl min Allah (connection with God) and habl min al-Nass (connection with others). The values inherent in this tradition align with the realms of insaniyah (humanitarian) and Ilahiyah (divine). By shedding light on the intricate interplay between Islam and local customs, particularly within the context of the sambelien tradition, this study enriches our understanding of the cultural tapestry that defines communities in the Malangsari area and beyond.